2014
DOI: 10.1016/j.jelechem.2013.07.017
|View full text |Cite
|
Sign up to set email alerts
|

On the behavior of CO oxidation on shape-controlled Pt nanoparticles in alkaline medium

Abstract: In this work, the behavior of the CO electro-oxidation reaction on shape-controlled Pt nanoparticles in alkaline medium was examined in order to understand the effect of the surface structure on this reaction. A series of experiments using Pt nanoparticles of different surface structures/shapes was used and the results obtained were compared with the previous knowledge gained from stepped platinum single crystal electrodes. Independently of the preferential orientation of the nanoparticles, the CO oxidation vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…Electrochemical techniques offer detailed information on the surface structure of shape-controlled metal nanoparticles based on a large number of nanoparticles that are available on the electrode surface (Solla-Gullón et al, 2004, 2008; Chen et al, 2012; Farias et al, 2014; García-Cruz et al, 2019; Mayet et al, 2019). Voltammograms characteritic of low-index planes on the surface of Pt nanoparticles in both acidic and alkaline electrolytes were recently reported in the literature (Vidal-Iglesias et al, 2012; Devivaraprasad et al, 2014; Jukk et al, 2017).…”
Section: Structure Sensitivity Of Orr With Single Crystal Electrodes mentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical techniques offer detailed information on the surface structure of shape-controlled metal nanoparticles based on a large number of nanoparticles that are available on the electrode surface (Solla-Gullón et al, 2004, 2008; Chen et al, 2012; Farias et al, 2014; García-Cruz et al, 2019; Mayet et al, 2019). Voltammograms characteritic of low-index planes on the surface of Pt nanoparticles in both acidic and alkaline electrolytes were recently reported in the literature (Vidal-Iglesias et al, 2012; Devivaraprasad et al, 2014; Jukk et al, 2017).…”
Section: Structure Sensitivity Of Orr With Single Crystal Electrodes mentioning
confidence: 99%
“…Thus, many research groups investigated electrooxidation of organic molecules (formic acid, carbon monoxide, methanol etc. ), hydrogen evolution, and oxygen reduction on low-index crystallographic planes of Pt and Pd (Housmans and Koper, 2003; Hoshi et al, 2006; Solla-Gullón et al 2008; Grozovski et al, 2010; Farias et al, 2014). In particular, the kinetics of ORR was found to be dependent on the exposed crystallographic planes ({hkl}) as reported with single crystal Pt and Pd surfaces and on electronic factors decided by the surface, subsurface and bulk compositions (Marković et al, 1994, 1995, 1997; Stamenkovic et al, 2002, 2006; Kondo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An additional characteristic of the voltammograms is that they contain, aside from the prevawe, a shoulder at low potentials followed by a peak at higher potentials. The general shape is almost independent of the shape of the nanoparticles, although the ratio of the different peaks and the exact peak position depends on the specific shape [75]. It Another difference with the acidic conditions is the small effect of the support in the stripping voltammogram.…”
Section: Co Oxidation On Pt Nanoparticles In Alkaline Mediamentioning
confidence: 99%
“…Finally, the presence of two peaks is the result of a nucleation and growth model. As the effect of different scan rates and partial stripping indicates [75], both peaks are interconnected. Peak potentials have the same scan rate dependence.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In the present case, it was found that the contrasting balances in activity of different sites caused by changing the (electro)chemical (solution) environment of a Pt catalyst was related to the type of site, and seemed to be influenced by the surface scale of the catalyst in question. From comparison of the voltammetric profiles for CO oxidation on shapecontrolled Pt nanoparticles in acid72 and alkaline73,74 solutions, it can be concluded that changing the solution pH from acidic to alkaline is accompanied by the promotion of all types of catalytic sites at nanoparticle surfaces. Hence, the contrasting balances in catalytic activity at low coordinated sites on extended Pt surfaces, compared to the (111) terraces, indicate that low coordinated sites on a stepped surface present different catalytic behavior, compared to low coordinated sites on a Pt nanoparticle.The solution pH also appeared to have different effects on the HUPD binding energy, depending on the site at stepped Pt surfaces.…”
mentioning
confidence: 99%